IMPLEMENTASI KONSEP TROPIS MODERN DALAM PERANCANGAN RUMAH SAKIT UMUM KELAS D PRATAMA KECAMATAN TOLITOLI UTARA - Misnandani, Misnandani; Rosid, Mohammad (Architecture Study Program, Faculty of Engineering, Madako University Tolitoli, 2024)
The importance of health access in the North Tolitoli area bordering Buol Regency, is quite far from the city center, making it difficult to refer patients to the main hospital. This condition underlies the design of the hospital, becoming an ideal solution to support health services and referrals from the Health Center. The research method used is qualitative with a case study approach and analysis of space requirements based on class D hospital service standards. Data collection techniques involve field observations, interviews with related parties, and document reviews including hospital design guidelines and government regulations. Data analysis was carried out using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The architectural approach with a modern tropical design concept, which is adjusted to the local climate and site conditions in North Tolitoli. This approach aims to create environmentally friendly, energy efficient, and functional buildings, taking into account natural air circulation, lighting, and the use of local materials. The results of the study show that this Class D Pratama Hospital is able to meet the health needs of the community by providing main rooms such as the Emergency Room, polyclinic, inpatient room, laboratory, and pharmacy. Architecture is required to continue to innovate and develop architectural designs that are adaptive to climate, including tropical climates, as well as improving the quality of health facilities in remote areas as a contribution to architectural science in the field of health facility design.